Clinical studies evaluating abametapir lotion, 0.74%, for the treatment of head louse infestation - Bowles, Vernon M.; VanLuvanee, Lisa Jenkins; Alsop, Hugh; Hazan, Lydie; Shepherd, Katie; Sidgiddi, Srinivas; Allenby, Kent; Ahveninen, Tiina; Hanegraaf, Sharon (Pediatric dermatology, 2018)
Background There is a need for better control of head louse infestations. Abametapir is an inhibitor of metalloproteinases critical for louse survival and egg development. The efficacy of abametapir lotion, 0.74%, was assessed for its ability to clear head louse infestations after a single application. Methods Two randomized, double‐blind, multicenter, vehicle‐controlled studies were conducted in subjects aged 6 months and older to compare the effectiveness of abametapir lotion versus vehicle control for eliminating head louse infestations without nit combing. Abametapir lotion was applied to dry hair for 10 minutes on day 0 and then rinsed with water. The primary endpoint was the proportion of index subjects (youngest household member with ≥ 3 live lice at screening) in the intent‐to‐treat population who were louse free at all follow‐up visits through day 14. Older household members with one or more live lice at screening were designated as nonindex subjects and treated as per the index subject within their household. Results In the intent‐to‐treat population (index subjects, N = 216), 81.5% of subjects treated with abametapir lotion were louse free through day 14 after a single treatment, versus 49.1% with vehicle (P < 0.001). For the combined index and nonindex population (N = 704), 85.9% were louse free through day 14 in the abametapir group, versus 61.3% in the vehicle group (P < 0.001). The most frequently reported adverse events were erythema (4.0%), rash (3.2%), and skin burning sensation (2.6%). Conclusion Abametapir lotion, 0.74%, was effective at clearing active head louse infestations through day 14 in subjects aged 6 months and older. All adverse events (including one serious but unrelated to study drug) resolved uneventfully.